2016
DOI: 10.1038/npjschz.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of synaptic pathology in the CA1 region in schizophrenia

Abstract: Alterations of postsynaptic density (PSD)95-complex proteins in schizophrenia ostensibly induce deficits in synaptic plasticity, the molecular process underlying cognitive functions. Although some PSD95-complex proteins have been previously examined in the hippocampus in schizophrenia, the status of other equally important molecules is unclear. This is especially true in the cornu ammonis (CA)1 hippocampal subfield, a region that is critically involved in the pathophysiology of the illness. We thus performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 76 publications
6
66
0
Order By: Relevance
“…In the present study we show that protein expression of the NMDA receptor subunits (NR1, NR2A and NR2B), group 1 mGluRs (total, dimeric and monomeric forms) and group 1 mGluR regulators (Norbin and Homer1b/c) are not altered in the NAcc in individuals who had schizophrenia, which is in contrast to previous reports on cortical and hippocampal brain regions. 9,[17][18][19] In agreement with our findings, previous studies examining NMDA subunit transcript expression and receptor binding within the NAcc reported no change to NR1, NR2A and NR2B. 11,12 Furthermore, no change in binding or mRNA expression of the other ionotropic glutamate receptors, aminomethylphosphonic acid and kainate, has previously been reported in the NAcc.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study we show that protein expression of the NMDA receptor subunits (NR1, NR2A and NR2B), group 1 mGluRs (total, dimeric and monomeric forms) and group 1 mGluR regulators (Norbin and Homer1b/c) are not altered in the NAcc in individuals who had schizophrenia, which is in contrast to previous reports on cortical and hippocampal brain regions. 9,[17][18][19] In agreement with our findings, previous studies examining NMDA subunit transcript expression and receptor binding within the NAcc reported no change to NR1, NR2A and NR2B. 11,12 Furthermore, no change in binding or mRNA expression of the other ionotropic glutamate receptors, aminomethylphosphonic acid and kainate, has previously been reported in the NAcc.…”
Section: Discussionsupporting
confidence: 81%
“…16 We recently identified that protein expression of group 1 mGluRs, particularly the dimeric form, was altered in 2 regions that innervate the NAcc and that were associated with the glutamatergic dysfunction of schizophrenia: the PFC and hippocampus. [17][18][19] Therefore, considering these regions send major glutamatergic projections to the NAcc and the recent evidence this system may be disrupted in individuals with schizophrenia, we hypothesized that these proteins may be altered in the NAcc of individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased HOMER1 knockout mice also showed somatic growth retardation, poor motor coordination, enhanced sensory reactivity, learning deficits and increased aggression in social interaction 218 Overexpression of HOMER1 in knockout mice reverted the cognitive and behavioural impairments 217 Exposure to novel environments upregulated HOMER1 mRNA in the hippocampus of rats 219 Methamphetamine or cocaine administration upregulated HOMER1 mRNA in the neocortex of rats 220 LSD or PCP administration upregulated HOMER1 mRNA in the PFC of rats 221,222 10Ketamine increased HOMER1 mRNA in the cortical regions, striatum and nucleus accumbens of rats 195,223 Antipsychotics (haloperidol, olanzapine or clozapine) induced an increment of Homer1 protein expression in the cortex, the striatum, the caudate-putamen or nucleus accumbens of rats 107,[224][225][226][227][228] de Bartolomeis et al 107 Matosin et al 189 de Bartolomeis et al 195 Leber et al 213 Inoue et al 214 Gerstein et al 215 Szumlinski et al 216 Lominac et al 217 Jaubert et al 218 Vazdarjanova et al 219 Fujiyama et al 220 Cochran et al 221 Nichols et al 222 Iasevoli et al 223 Iasevoli et al 224 Iasevoli et al 225 Ambesi-Impiombato et al 226 Polese et al 227 Tomasetti et al …”
Section: Homer1mentioning
confidence: 99%
“…Increased DLG4 mRNA and decreased protein expression in ACC of schizophrenia patients 177 Increased DLG4 mRNA and protein expression in thalamus of schizophrenia patients 182,185 Increased DLG4 mRNA expression in the occipital cortex of schizophrenia patients 186 Decreased DLG4 mRNA expression in the PFC of schizophrenia patients 69 Decreased DLG4 mRNA and protein expression in the DLPFC of schizophrenia patients 187 Decreased DLG4 protein expression in thalamus of schizophrenia patients 182 Decreased DLG4 protein expression in hippocampus 188,189 Decreased mRNA expression in the striatum 190 No changes in either DLG4 mRNA or protein expression in PFC of schizophrenia patients 175,186 No changes in either DLG4 mRNA or protein expression in the hippocampus of schizophrenia patients 69,182 DLG4 mutant mice displayed schizophrenia and autism-spectrum disorder-like phenotypes 184 DLG4 mutant mice displayed aberrant AMPA receptor-mediated transmission 178,191 DLG4 mutant mice exhibited enhancement in LTP and deficit in LTD 178,[192][193][194] DLG4 mutant mice exhibited disrupted synaptic plasticity and impaired learning 192 Ketamine reduced DLG4 mRNA in cortical regions of rats 195 Ohnuma et al 69 Toyooka et al 175 Kristiansen et al 177 Carlisle et al 178 Clinton et al 179 Clinton et al 182 Feyder et al 184 Clinton et al 185 Dracheva et al 186 Funk et al 187 Toro et al 188 Matosin et al 189 Kristiansen et al 190...…”
Section: Dlg4mentioning
confidence: 99%